O iNaturalist como ferramenta no estudo de abelhas indígenas sem ferrão (Apidae, Meliponini) no estado de São Paulo, Brasil - Aranda, Bruno Henrique (2024)
©iNaturalist is a multi-taxa platform that allows anyone to record photos or sounds of different species anywhere in the world, along with their respective geographical locations, while experts assist in identifying the records, which are made available to society. The platform is based on the methodology of citizen science, which involves and engages society in scientific investigations. Bees from the Meliponini tribe are extremely numerous in the American tropics, both in terms of species and individuals, playing an important role in pollinating the native vegetation of these regions. Brazil is considered one of the countries with the greatest diversity of these bees; however, there are still knowledge gaps about the group. Given their important ecological role and the numerous anthropogenic impacts threatening the group, obtaining scientifically relevant data using citizen science can significantly contribute to the conservation of these bee species. In this context, the aim of this work was to investigate the observations of Meliponini bees present on the ©iNaturalist platform to assess the feasibility and reliability of the available data as a source for future studies on the group. For this purpose, only observations of the taxon Meliponini classified with a "research grade" status (observations with photo, location, date, and agreement of at least ⅔ of the identifiers) entered in the platform until 31/12/2022, georeferenced to the state of São Paulo, were considered. The validation of the status was done after reviewing the identification of each observation using specific literature and with the assistance of platform specialists and invited experts. A total of 953 observations were found, from 26 species belonging to the group. After reviewing the raw data, three observations were identified as "duplicates" and were subsequently deleted by users, resulting in a total of 950 observations to be evaluated. In this study, we adopted a standardized evaluation criterion that consisted of classifying the observations as: (HA) High Accuracy, for those that, after our evaluation, remained at the species level; (AA) Average Accuracy, for those that needed to return to the genus level; (LA) Low Accuracy, for those that needed to return to the tribe level. Out of the total observations, 917 (96.5%) were assessed as (HA), demonstrating a high degree of reliability of the data present on the platform for this group, indicating the potential of this tool to contribute to studies on Meliponini. After the evaluation, we sought to identify and extract additional information from all observations classified as (HA), which were gathered into two main theme records: "nests" (n=422, 54.38%) and "interactions" (n= 354, 45.61%). Such information was categorized within the respective themes, and based on this, we suggested possible applications of the data present on the platform for studies related to the group. Considering the opportunities and challenges encountered throughout the validation process of the observations, we also indicated some strategies aimed at improving the quality of future records involving bees of the Meliponini tribe and aiming to promote the expansion of the national scientific community's participation on the platform.